J.K. Lasser's small business taxes 2018 : your complete guide to a better bottom line - Weltman, Barbara, 1950- (J.K. Lasser--practical guides for all your financial needs, 2018)
Maximize your bottom line with the nation's most trusted small business tax guide J.K. Lasser's Small Business Taxes 2018 is the small business owner's ultimate guide to a money-saving, stress-free tax season. Providing straightforward advice from the nation's most trusted tax expert on small business taxes, this book gives you the answers you need quickly, with clear, concise guidance. Updated and expanded to cover new and changing tax law, this edition also includes an e-supplement covering the latest developments from Congress and the IRS to keep you fully up-to-date. A complete listing of all available business deductions and credits helps you identify those you qualify for, and includes critical information on dollar limits, recordkeeping requirements, and how to actually take the write-off--all the way down to which line on which form. Organizational and planning strategies help you get through the process quickly and with fewer headaches, and this year's changes to the tax laws are explained in terms of how they affect your filing. Keeping up with the intricacies of tax law and filing is a full-time job--but it's not your full-time job. You have a business to run. This book gives you the guidance you need in the time that you have so you can get taxes out of the way and get back to work. Learn which expenses qualify for deductions--and which ones don't Adopt a more organized recordkeeping system to streamline the filing process Explore small-business-specific strategies for starting or closing a business, running a sideline business, and operating in multiple businesses Decode the various forms and worksheets correctly with step-by-step guidance Review obligations for the 'other taxes,' including payroll and excise taxes Every year, millions of small business owners overpay their taxes because they lack the time and expertise to make tax-sensitive business decisions throughout the year only to learn that it's too late to act when it comes to tax time. Now you can put your money back where it belongs--in your business. J.K. Lasser's Small Business Taxes 2018 helps you take wise actions during the year and tells you how to file completely and accurately while maximizing your bottom line.